Antibacterial and quorum sensing regulatory activities of some traditional Eastern-European medicinal plants - Tolmacheva Anna A.; Rogozhin Eugene A.; Deryabin Dmitry G. (Acta Pharmaceutica)
The objective of this study was to screen extracts of twenty Eastern European medicinal plants, using wild-type and reporter Chromobacterium violaceum bioassays, for novel components that target bacterial cells and their quorum sensing (QS) communication systems. Three types of activity and their combinations were revealed: (i) direct antimicrobial growth-inhibitory activity, (ii) non-specific and specific pro-QS activities, (iii) anti-QS activity. Among seven plant extracts showing direct growth-inhibitory activity, the strongest effect was shown by Arctostaphylos uva- -ursi (bearberry) leaves. Many plants stimulated violacein production by wild-type C. violaceum ATCC 31532 in a non-specific manner, and only the herb Bidens tripartita (three-lobe beggarticks) contained compounds that mimic acyl-homoserine lactone and operated as a QS agonist. Anti-QS activity was found in eleven plants including Quercus robur (oak) cortex, Betula verrucosa (birch) buds and Eucalyptus viminalis (Manna Gum) leaves. Subsequent statistical analysis showed differences between antimicrobial and anti-QS activities, whereas both activities were defined by phylogenetic position of medical resource plant. Finally, extract from Quercus robur cortex revealed at least two fractions, showing different anti-QS mechanisms. These data confirm that multicomponent anti-infectious mechanisms are used by plants, which may be useful for drug development